Toshiba / Mohd Aizuddin Mohd Rahim - Mohd Rahim, Mohd Aizuddin (2022)
This task is about identifying problems with a product. The company that has been my choice is Toshiba. Of the various products that have been released by this Toshiba company, I have chosen the Thrive Tablet to do my analysis. In this case study, I have performed a SWOT Analysis to identify the strengths, weaknesses, opportunities, and threats of this product. The main problem I have identified with this product is short battery life. Through out of that problem, I was able to come up with the best solution that made this tablet usable for quite some time.